Studies on a cell culture derived from hepatopancreas of tiger prawn Penaeus monodon - Manohar, B Murali; Vivek, K V; Kumanan, K (Indian Journal of Fisheries, 2011)
Hepatopancreatocytes from hepatopancreas of penaeid shrimp, monodon werecultured in artificial medium Leibovitz-15, supplemented with glucose andsodium chloride in vitro. Two different approaches for culturing of these cells werefollowed, i) Culturing, enzymatically disrupted cells and ii) Explant culture ofsmall tissue fragments. The second approach of explant cultures was observed tobe highly adva- ntageous as a monolayer was observed within 4-6 days of culture.On the whole, cells could be maintained for as long as 45 days with a maximumof 5 passages. On subculturing, generally one subpopulation of cells with highproliferative capacity was observed to be predominant. Morphological studieslead to the conclusion that these cells were embryonic cells from the tubularepithelium of hepatopancreas.